Carbon Footprint and Sustainability: Assessment and Optimization in Urban Development - Naeema Nazar; Aeliswa Raju; Alex Benny; Ranjeesh R Chandran (International Journal of Engineering and Management Research, 2024)
As urbanization accelerates globally, the environ- mental impact of cities has become a growing concern, particularly regarding their carbon emissions. This paper analyzes the carbon footprint associated with urban development, identifying key emission sources such as energy use, transportation, and construction. The study assesses current sustainability initiatives and highlights the potential for improvement through innovative strategies. By focusing on optimizing urban planning with low- carbon technologies, the research offers practical solutions to reduce emissions without hindering urban growth. The findings emphasize the importance of integrating green infrastructure and effective policies to achieve a balance between urban expansion and environmental sustainability.